2021
DOI: 10.15386/mpr-1692
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of DNA damage in tobacco associated human buccal cells using comet assay

Abstract: Aim and objective. To assess the DNA damage in tobacco associated human buccal cells using comet assay. Methods. The study included 75 study subjects, which were divided into 3 groups on the basis of tobacco usage. Group I - 25 individuals with no history of tobacco usage, Group II - 25 individuals with tobacco usage but without oral lesions and Group III - 25 individuals with tobacco associated oral lesions. Cytological smears collected from these individuals were used to assess the tobacco associated D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…It is also known as cyclin-dependent kinase inhibitor 2A (CDKN2A). The overexpression of P16 has been reported in several studies investigating oral cancer [ 7 ]. P53, on the other hand, is a tumor suppressor protein involved in regulating cell cycle progression and preventing the formation of tumors [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also known as cyclin-dependent kinase inhibitor 2A (CDKN2A). The overexpression of P16 has been reported in several studies investigating oral cancer [ 7 ]. P53, on the other hand, is a tumor suppressor protein involved in regulating cell cycle progression and preventing the formation of tumors [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The association between smoking and the overexpression of P16 and p53 proteins in various tissues has been investigated in many studies. For example, Sunberg et al [7] found a significant increase in P16 expression among smokers compared to nonsmokers in oral squamous cell carcinoma. Similarly, Liu et al [11] reported a positive correlation between smoking and p53 overexpression in oral leukoplakia [12,13].…”
Section: Introductionmentioning
confidence: 99%